An Unusual Complication of Suprapubic Catheter Migration into the Left Ureter - Shuaibin, Wang; Haiqi, Mu; Qin, Feng; Haifeng, Yu (Urology Journal, 2018)
Suprapubic cystostomy is a widely employed procedure that is used to drain the bladder. Despite being a safe procedure, suprapubic cystostomy has been reported to present multiple intra- and postoperative complications. Serious and unusual complications can occur during changing of the suprapubic catheter (SPC) in patients with neuropathic bladder. In this work, we report an elderly patient with neuropathic bladder suffering from an unusual complication involving migration of the SPC into the ureter during changing of the SPC, leading to ureteric obstruction and left pyelonephritis.